Effect of Spent Coffee Grounds on the Organoleptic Properties, pH, Moisturizing Effect, and Skin Irritation of Body Scrub Formulated with Waste Cooking-Olive Oils Liquid Soap - Syamsul Bakhri; Lastri Wiyani; Dhea Kirana Faradila Amir; Rilda Yasifa Idznih; Isna Rahmayanti Burhanuddin; Rewnita Shahra Asmin (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2026)
Spent coffee grounds (SCG) have potential as a sustainable exfoliating material for body scrub formulations. This study evaluated the effects of systematically varying the proportions of SCG and liquid soap derived from waste cooking oil and olive oil on the organoleptic properties, pH, moisturizing effect, and skin irritation responses of body scrubs. Three formulations containing 3% cornstarch were prepared with SCG and liquid soap proportions of 40:57% (V1), 50:47% (V2), and 60:37% (V3), respectively. Organoleptic properties were evaluated descriptively, pH was measured in triplicate, and moisturizing and irritation responses were assessed observationally in 13 respondents. Increasing SCG progressively changed the texture from smooth (V1) to moderately coarse (V2) and coarse (V3), while all formulations exhibited a coffee odor and black color. The pH values were 7.87 0.23, 7.70 0.07, and 7.38 0.38 for V1, V2, and V3, respectively, all within the pH range of 4.5–8.0 adopted according to SNI 16-4399-1996, with no significant differences among formulations [one-way ANOVA, F(2,6) = 2.781, p = 0.140]. Positive moisturizing responses were observed in all respondents for V1 and V2 (13/13; 100%), but not for V3 (0/13; 0%). No itching, erythema, or edema was observed for any formulation during the 30-min observation period. Overall, V1 exhibited the most favorable combination of characteristics among the formulations evaluated. These findings indicate that the SCG–liquid soap compositional balance is an important formulation factor influencing the physicochemical and observed skin-response characteristics of SCG-based body scrubs.